Role of the Family in Children’s Remote Learning Experiences during the COVID-19 outbreak: Kazakhstan and Hungary - Csonka-Stambekova, Assel (Psihološka istraživanja, 2021)
The COVID-19 outbreak forced schools around the globe to close. As a result, home became the dominant learning environment and family members became educational providers for students. Research to date demonstrates that families responded differently to the challenges related to remote learning and demonstrated various responses in their new responsible roles. Furthermore, research from the initial phases of COVID-19 shows that families’ socio-economic status and educational background are related to children’s remote learning experiences. This study seeks to explain and advance our understanding of the participants’ remote learning experiences in the early stage of COVID-19 through the analysis of three Kazakhstani and three Hungarian families. The families have different backgrounds, including the language they speak, their residential characteristics, parents’ educational attainment, and occupational status. The author conducted semi-structured interviews with parents from Kazakhstan and Hungary via Zoom. Qualitative directed content analysis was employed to analyse the collected data. The results of this study indicate that: a) parents had to become teachers in addition to their primary caregiver roles, thus balancing parenting and home-schooling; b) children’s learning opportunities and losses during the COVID-19 outbreak are linked to families’ socioeconomic status; and c) some families found it difficult to support their children due to their lack of pedagogical and content knowledge. Therefore, it can be concluded that existing social and educational inequalities in Kazakhstan and Hungary may have long-lasting negative effects on the children who did not experience high levels of parental involvement in their remote education.